EVALUATION OF IN-VITRO VASORELAXANT EFFECT (POTENTIAL ANTIHYPERTENSIVE) OF KIGELIA AFRICANA FRUIT METHANOL EXTRACT ON POTASSIUM CHLORIDE AND PHENYLEPHRINE INDUCED TENSION IN WISTAR RAT AORTA - Isah, A. O.; Idu, M.; Abdulrahman, A. A.; Amaechina, F. (FUDMA JOURNAL OF SCIENCES, 2020)
This research on Kigelia africana was conducted in order to ascertain its ability to relax excited vascular smooth muscle in rat aorta. Preliminary investigation on whether the plant exhibits antihypertensive property was done before the evaluation of in vitro vasorelaxant effect. The vasorelaxant activity was determined using in vitro method on rat aorta with the aid of perfusion apparatus with a detachable organ bath. The administration of potassium chloride (KCl) raised the tension from 1.0 to 1.31 indicating that the aorta got to its peak of contraction. At 10 and 20mg/kg, the tension dropped significantly, showing relaxation of the smooth muscle while at 5mg/kg, drop in tension was insignificant at pË‚0.05. However, at some of the doses, towards the end of experiment, there was steady resurge in tension showing that the aorta resumed contraction. On the application of phenylephrine (PE), the tension rose to 1.18g. On administration of the extract, the tension dropped slightly showing mild vascular smooth muscle relaxation. From the results obtained, there was seeming similarity in the action of the K. africana compared to amlodipine/Ramipril in KCl and PE induced tension in aorta respectively. However, at 10 and 20mg/kg, a substantial decrease in tension was noted indicating that the extract action is dose dependent. Thus, from this in-vitro smooth muscle relaxation study in rats, the methanol extract of K. africana has depressant property that was likely expressed by enhancing the closing of voltage operated calcium channel and ACE inhibiting activity in KCl and Phenylephrine induced tension respectively.